Penyuluhan Pemutaran Media Animasi terhadap Pengetahuan, dan Sikap tentang Jajanan Sehat sebagai Upaya Pencegahan Diare pada Anak Usia - Nasution, Sri Wahyuni; Ginting, Chrismis Novalinda; Saragih, Jean (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to see the effect of animation media screening counseling on knowledge and attitudes about healthy snacks as an effort to prevent diarrhea in school-age children. The research method is quantitative with a pre-experimental design with one group pre-and post-test. Data were collected using observation sheets. Data were analyzed using the Wilcoxon test. The results showed that the mean knowledge score about healthy snacks before and after animation media screening counseling was 20.27 ± 1.461 and 23.07 ± 0.740. The mean score of attitudes about healthy snacks before and after animation media screening counseling was 38.43 ± 2.648 and 43.83 ± 2.291. The conclusion of this study is that animation media screening counseling has an effect on knowledge and attitudes about healthy snacks as an effort to prevent diarrhea in school-age children. Keywords: School-Age Children, Healthy Snacks, Animation Media, Knowledge, Attitude